Wall Material Formulations for Zingiberaceae family Rhizome Extracts (Curcuma longa, Curcuma xanthorriza and Zingerol officinale) on Microencapsulation Efficiency of Spray Drying Processing - Jaidi, Eisya Umaira; Mad Nordin, Mariam Firdhaus; Mohd Kassim, Angzzas Sari (Progress in Engineering Application and Technology, 2023)
Research has found that Curcuma sp. (Curcuma xanthorrhiza, Curcuma longa and ginger) contain bioactive compound that possesses antioxidant, antimicrobial and anti-inflammatory properties. The advancement of bring out bioactive compound from traditional medicine into modern medicine have been proceed. The process to encapsulate the extracted bioactive compound is spray drying. This study has been continued by formulating different wall material such as gum Arabic, xanthan gum and maltodextrin. The wall materials have been proposed in order to determine the properties of each wall material and how it affected the microcapsules (product). The best wall material formulation was determined by yield analysis, size distribution, moisture content, colour, functional group and the efficiency of microencapsulation. The wall material based (R3) shows the best formulation as compared to other running (R1, R2, R4, R5 and R6). The yield of R3 was quiet high which almost 24.88%. It was stated that the wall material based is an appropriate to be as an encapsulating agent for Curcuma longa. For color analysis, R3 was shown high yellow tendency. The yellow tendency is a parameter to indicate which microcapsules that contain a high amount of bioactive compound. Next is size distribution analysis. From this part, the appropriate of wall material formulation will be determined as the decreasing the D(90) value, the better of microcapsules have been produced. However, for moisture content analysis, the Curcuma sp. was not the highlighted one. The wall material used have to be concerned because the coating a main role in this analysis. The gum Arabic was stated as good wall material for curcumin microcapsules. Besides, functional group contained in each running was -OH which is alcohol. Lastly, the highest percentage of efficiency was R3 which it was proved that wall material based is the suitable one with Curcuma longa.  As a conclusion, this paper was successfully microencapsulated the extracted bioactive compound with different wall material formulation.